PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Bayu Wirayanti, Fransiska; Wirianata, Henny (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2024)
The value of the company will be reflected through the company's shares. This study aims to test the profitability variables measured by return on assets (ROA), liquidity measured by current ratio (CR), company size measured by firm size (FS), and company growth measured by assets growth (AG) on the company's value. The sampling technique was purposive sampling. The data used are consumer non-cyclical companies listed on the IDX for the 2019-2023 period. Consumer non-cyclical companies are part of the manufacturing industry. Consumer non-cyclical companies are engaged in basic necessities, cigarettes and beauty. The data was processed using Eviews 12 and Microsoft Excel software. It is hoped that this research can provide considerations in decision making regarding variables that can increase company value. The conclusion of this study is that profitability has a significant positive effect on company value. Variable liquidity, company size and growth have no significant effect on company value.